Evolution of temporal and spectral dynamics of pathologic high‐frequency oscillations (pHFOs) during epileptogenesis. (30th October 2015) - Jones, Ryan T.; Barth, Albert M.; Ormiston, Laurel D.; Mody, Istvan
Summary: Objective: In temporal lobe epilepsy (TLE), pathologic high frequency oscillations (pHFOs, 200–600 Hz) are present in the hippocampus, especially the dentate gyrus (DG). The pHFOs emerge during a latent period prior to the onset of spontaneous generalized seizures. We used a unilateral suprahippocampal injection of kainic acid (KA) mouse model of TLE to characterize the properties of hippocampal pHFOs during epileptogenesis. Methods: In awake head‐fixed mice, 4–14 days after KA‐induced status epilepticus (SE), we recorded local field potentials (LFPs) with 64‐channel silicon probes spanning from CA1 alveus to the DG hilus, or with glass pipettes in the DC mode in the CA1 str radiatum. Results: The pHFOs, are observed simultaneously in the CA1 and the DG, or in the DG alone, as early as 4 days post‐SE. The pHFOs ride on top of DC deflections, occur during motionless periods, persist through the onset of TLE, and are generated in bursts. Burst parameters remain remarkably constant during epileptogenesis, with a random number of pHFOs generated per burst. In contrast, pHFO duration and spectral dynamics evolve from short events at 4 days post‐SE to prolonged discharges with complex spectral characteristics by 14 days post‐SE. Simultaneous dural EEG recordings were exceedingly unreliable for detecting hippocampal pHFOs; therefore, such recordings may deceptively indicate a "silent" period even when massive hippocampal activity is present. Significance: Our results demonstrate that hippocampal pHFOs exhibit a dynamic evolution during the epileptogenic period following SE, consistent with their role in transitioning to the chronic stage of TLE.